Analysis of Atmospheric Aerosol and NO2 during the Stubble Burning Period Using Satellite Data over Haryana and Punjab States, India - Kumar, Sonu; Saini, Tek Chand (International Journal of Aquatic Research and Environmental Studies, 2026)
This study evaluate the spatio-temporal occurrence of agricultural residues burning impact on aerosols during one rice crop harvesting season (September to December 2018) over Haryana and Punjab State, India.OMI (Ozone monitoring instrument) AOD 342.5µm daily aerosol product and daily active fire data from  The impact of stubble burning on the aerosol distribution was found to be significant and it was observed more for residue burnt sites. Increase in concentration of aerosols during the paddy harvesting period especially when the fire counts were highest was observed due to increase in dust particle and precursor pollutants. The increased number of fire counts (with the help of Terra and Aqua MODIS data) is associated with severe aerosol-loading atmospheres (AOD342.5 nm > 1.5) over the Haryana and Punjab region, high values of high Aerosol Optical depth (~1.5) and NO2 concentrations (~8 × 1015 mol/cm2 ), indicating the dominance of smoke aerosols from agricultural crop residue burning.  The aerosol and NO2 was very high during burning period compared to that in pre burning and post burning period indicating that burning of rice residue is havingsignificant role in aerosol loading. The increase in aerosol shows its potential effect on air quality, climate and risk on human health. The spatial distribution of aerosols was also analyzed in GIS.